2021
DOI: 10.12962/j26151847.v5i2.14500
|View full text |Cite
|
Sign up to set email alerts
|

Analisa Peluangan Investasi dalam Pemanfaatan Aset Daerah Eks Puskesmas Oro-Oro Ombo di Kota Madiun

Abstract: Ketersediaan Aset Pemerintah Kota Madiun merupakan suatu potensi yang dapat dioptimalkan untuk menumbuhkan perekonomian apabila dikembangkan dengan baik. Lahan Bekas Puskesmas Oro-Oro Ombo milik Pemerintah Kota Madiun terletak di lokasi yang strategis, dan apabila dimanfaatkan dengan tepat dapat menjadi penggerak kegiatan ekonomi. Kajian ini untuk mengetahui peluang investasi yang dapat ditawarkan kepada investor dengan menggunakan metode Net Present Value (NPV), Internal Rate of Return (IRR), Profitability In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(3 reference statements)
1
1
0
Order By: Relevance
“…The results of this research are in line with previous research, which found that increasing communication and collaboration between the parties involved as well as optimizing the use of communication technology can provide significant benefits in managing regional assets (Santoso et al, 2021). This indicates that regional asset management will run better if there is effective coordination between relevant agencies, a clear understanding of the duties and responsibilities of each party, and open and transparent communication.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of this research are in line with previous research, which found that increasing communication and collaboration between the parties involved as well as optimizing the use of communication technology can provide significant benefits in managing regional assets (Santoso et al, 2021). This indicates that regional asset management will run better if there is effective coordination between relevant agencies, a clear understanding of the duties and responsibilities of each party, and open and transparent communication.…”
Section: Discussionsupporting
confidence: 87%
“…The results of this research are in line with previous research, which found that regional asset management carried out optimally by paying attention to the principles of efficiency, effectiveness, transparency, and public accountability has a positive impact on the orderly administration of regional assets, efficiency, and effectiveness in the use of regional assets, safeguarding regional assets, and availability of accurate and up-to-date information regarding regional assets (Wicaksana et al, 2021). Subsequent research also found that optimal management and utilization of regional assets can trigger regional economic growth (Santoso et al, 2021). In the context of implementation, the Regional Secretariat of South Solok Regency received the mandate to implement regional regulations regarding the management of regional property.…”
Section: Discussionmentioning
confidence: 93%